Hubungan penyakit infeksi dan ketahanan pangan keluarga terhadap status gizi balita di puskesmas kalimanah purbalingga - Ramadani, Khonsarizka Ayu; Sodikin, Sodikin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: To figure out the correlation between infectious diseases and family food security to the nutritional status of toddlers in Public Health Care Center of Kalimanah, Purbalingga. Method: Quantitative descriptive with cross sectional approach was used in this research. The sample in this study were toddlers aged 1-5 years in Kalimanah Purbalingga. There were 106 respondents. The samples were taken by simple random sampling technique. The data were analyzed by using Chi Square test. Results: The results of research on infectious diseases on the nutritional status of toddlers obtained the value (OR) = 0.837. While the results of family food security on the nutritional status of toddlers obtained the value (OR) = 4.121. Therefore, it can be stated there was a correlation between infectious diseases and family food security to the nutritional status oftoddlers. Conclusion: There is a correlation between infectious diseases and family food security to the nutritional status of toddlers in Public Health Care Center of Kalimanah, Purbalingga. keywords :infectious diseases, food security, nutritional status, toddlers